Bonded Joint Strength Prediction by the Inverse Method - Viana, F. A. L.; Campilho , R. D. S. G.; Rocha, R. J. B. (Techniques and Innovation in Engineering Research and Technology Vol. 5, 2023)
Adhesive joints have gradually replaced several traditional bonding techniques in industrial applications during the past few years. In this chapter, the cohesive laws of three adhesives, Araldite® AV138, Araldite® 2015 and Sikaforce® 7752, were obtained by the application of an inverse adjustment method between the numerical and experimental load-displacement curves (P-\(δ\)) of Double-Cantilever Beam (DCB) tests for tensile characterization and End-Notched Flexure (ENF) tests for shear characterization. These rules were then confirmed using Abaqus® with experimental data from single-lap joints (SLJ) and double-lap joints (DLJ). The triangle law accurately anticipated the SLJ and DLJ behaviour for the Araldite® AV138 and Araldite® 2015.